Formulasi Sediaan Blush on Cream Dengan Pewarna Ekstrak Kelopak Bunga Rosella (Hibiscus sabdarifa): Formulation of Blush on Cream Preparations with Rosella Flower Petals Extract Colorant (Hibiscus sabdarifa) - Dwi Agustina; Wisnu Cahyo Prabowo; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Blush is a type of decorative cosmetic used to give red color in the cheeks area so that the face looks prettier, fresh and dimensional. Currently there are many blush on in the market that contain hazardous chemicals. Then a blush on made from Rosella flower extract (Hibiscus sabdariffa) containing anthocyanin pigments uses as a safer dye alternative. This blush on cream formula made using Rosella flower extract with concentrations of 1%, 3%, and 5% with the resulting color of pale pink, pink and purplish pink. Evaluations test undertaken include organoleptic test, homogeneity test, spreadability test, pH test, viscosity test and stability test. The results obtained based on organoleptic test, homogeneity test, spreadability test, pH test, viscosity test shows that all three formulas entered into the required range of values.